Respuesta :

Answer:

−4x−6

Step-by-step explanation:

Distribute the Negative Sign:

=2(x+2)−x+3(−x−2)+−1(2x+4)

=2(x+2)+−x+3(−x−2)+−1(2x)+(−1)(4)

=2(x+2)+−x+3(−x−2)+−2x+−4

Distribute:

=(2)(x)+(2)(2)+−x+(3)(−x)+(3)(−2)+−2x+−4

=2x+4+−x+−3x+−6+−2x+−4

Combine Like Terms:

=2x+4+−x+−3x+−6+−2x+−4

=(2x+−x+−3x+−2x)+(4+−6+−4)

=−4x+−6

Answer:

-4x - 6

Step-by-step explanation:

2(x+2)−x+3(−x−2)−(2x+4)

Distribute the Negative Sign:

=2(x+2)−x+3(−x−2)+−1(2x+4)

=2(x+2)+−x+3(−x−2)+−1(2x)+(−1)(4)

=2(x+2)+−x+3(−x−2)+−2x+−4

Distribute:

=(2)(x)+(2)(2)+−x+(3)(−x)+(3)(−2)+−2x+−4

=2x+4+−x+−3x+−6+−2x+−4

Combine Like Terms:

=2x+4+−x+−3x+−6+−2x+−4

=(2x+−x+−3x+−2x)+(4+−6+−4)

=−4x+−6